ANALISIS LAPORAN KEUANGAN MENURUT PSAK 01 PADA PT METROPOLITAN KENTJANA TBK - Ayu Fitri Rosianie; Edi Kurniawan (Institut Teknologi dan Bisnis Swadharma, 2021)
Financial statement analysis is used to determine the company's financial performance as a consideration in making decisions and evaluating the company's financial performance for the next period. However, the financial statements prepared by each company do not fully meet the applicable accounting standards and principles. For this reason, the accounting process requires Financial Accounting Standards (SAK) that contains guidelines for every transaction made by the company. This standard allows interested parties to interpret and compare its financial statements with other companies. PT Metropolitan Kentjana Tbk has been able to present information about the basis for preparing financial statements, providing information that has not been presented in the financial statements including displaying the general description of the company, accounting policies, and an overview of accounting policies, and others. This shows that the financial statements of PT Metropolitan Kentjana Tbk for the notes to the financial statements have met the existing standards. The financial statements presented by PT Metropolitan Kentjana Tbk have met the requirements in PSAK 01